Endosymbionts impact ladybird predation rates of aphids in a temperature-dependent manner - Katrine Bitsch; Perran A. Ross; Alex Gill; Qiong Yang; Monica Stelmach; Ashley G. Callahan; Michael Ørsted; Ary A. Hoffmann; Torsten N. Kristensen (BioControl, 2025)
Aphids are pests that cause major economic losses to growers on a global scale. Current management strategies rely heavily on pesticides, but some effective pesticides are being withdrawn, and the efficiency of remaining pesticides is decreasing, as aphids build up resistance. Biological control using predators can provide an important sustainable alternative to pesticides under some circumstances, and the deliberate introduction of facultative bacterial endosymbionts that induce host fitness costs and reduce plant virus transmission has been suggested as another strategy to combat aphid damage. However, new control options should not be antagonistic, and there might be a concern that the effectiveness of biocontrol can be altered/reduced by endosymbiont presence in hosts. We therefore tested if predation by two ladybirds, Adalia bipunctata and Harmonia conformis , on green peach aphid, Myzus persicae, and oat aphid, Rhopalosiphum padi , was affected by transinfected Rickettsiella viridis and Regiella insecticola endosymbionts and we used different temperatures to assess if any effects depended on temperature. The predation rate (defined as the time it takes for ladybirds to capture and eat the aphids) of aphids infected by either endosymbiont was higher at 14 °C compared to the rate at which uninfected aphids of both species were eaten. The opposite pattern was seen for both aphid species at 20 °C and for one host-endosymbiont combination at 26 °C. Aphids were eaten faster at 26 °C compared to at the lower temperatures, while differences in predation rates between 14 °C and 20 °C depended on species. Another important outcome of our study was that transmission of endosymbionts from aphids to ladybirds did not occur. Our findings reveal a highly temperature-dependent effect of the investigated endosymbionts on ladybird predation rates on aphids. The temperature dependence of endosymbiont-predation interactions suggests that seasonal climatic variation should be considered when assessing the impact of endosymbionts in settings where biological control is important.